Symptomatic Control in End-of-Life Patients - Alves, Mariana (2017)
End-of-life patients present a variety of symptoms that cause suffering for them and their respective families. Health professionals throughout their university, internship and medical careers are ill-prepared to manage and improve the quality of life of these patients. This article aims to provide basic skills in the symptomatic management of end-of-life patients, focusing in particular on the control of pain, dyspnoea, fatigue, nausea, vomiting and anorexia. It also aims to draw attention to basic concepts of control concerning refractory symptoms and palliative sedation.